Analisis Pengaruh Penggunaan Facebook Bagi Mahasiswa dan Hubungannya dengan Gangguan Kecanduan Facebook - Ronal Watrianthos; Ibnu Rasyid Munthe; Rahma Muti’ah (STMIK Budi Darma, 2019)
Along with the rapid development of Social Networking Sites (SNS), social media, recently, has become a lifestyle for many people around the world, including in Indonesia. The data in January 2018 showed that in Indonesia out of 132.7 million internet users, almost all (131 million), or up 23% from the data in 2017, were Facebook users with the dominance of 18-24 years old, 35% of whom were the highest active users. The rapid growth of Facebook users annually in Indonesia, especially in the age of students and college students, encourages researchers to conduct many empirical studies of Facebook use among students. There is a tendency for using Facebook continuously to create FAD effects (Facebook Addiction Disorder) among students and can affect the spirit of learning. This study also discusses what is the motivation for using Facebook and seeing the potential for FAD to occur. In this study, an online survey over 375 respondents from several students in Labuhanbatu District was conducted. To explore respondents' motives in using Facebook, respondents were given questions that were divided into the following five motives: social interaction, leisure time, entertainment, friends, and communication. While to look for potential addiction, respondents were given questions using the Bergen Facebook Addiction (BFAD) scale. In getting a connection between the motives for using Facebook and Facebook Addiction, the data was tested by analysis of variants (ANOVA) and partial tests using SPSS software. The results obtained were 65.8% of participants were at a moderate level, while 20.3% were at a low level, and only 13.9% of participants were at a high level. While the most significant motive affecting respondents in using Facebook is the motive to fill the time and motives for communicating.